Enriching gluten-free rice pasta with soybean and sweet potato flours - Marengo, M.; Amoah, I.; Carpen, A.; Benedetti, S.; Zanoletti, M.; Buratti, S.; Lutterodt, H.E.; Johnson, P.T.; Manful, J.; Marti, A.; Bonomi, F.; Iametti, S. (Springer, 2018)
The development of innovative rice products is a way to exploiting and adding value to low-grade African rice varieties. To this purpose, rice-based pasta was enriched with flours from soybean and orange-fleshed sweet potato, that are common ingredients in the African tradition. Four different formulations based on pre-gelatinized rice flour and liquid egg albumen, and containing soybean and/or sweet potato (up to 20%) were prepared and characterized via a multidisciplinary approach. Soybean and sweet potato enrichment leads to a decrease in the pasta consistency and in significant changes in the color of the resulting samples, likely due to Maillard-type reactions. E-sensing approaches indicated that the sensory profile of the various pasta products strongly depends on the type of enrichment. Data collected after cooking suggest that both soybean and sweet potato have a role in defining the firmness and water absorption, as well as the optimum cooking time. Structural characterization of proteins in the uncooked products indicates the presence of protein aggregates stabilized by hydrophobic interactions and disulfide bonds in all samples, although structural properties of the aggregates related to specific compositional traits.